2010
DOI: 10.1007/s11738-010-0649-9
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of jasmonates and ethylene on inhibition of Pharbitis nil flowering

Abstract: Interactions between methyl jasmonate (JA-Me) and ethylene in the photoperiodic flower induction of shortday plant Pharbitis nil were investigated. Both JA-Me and gaseous ethylene applied during the inductive long night caused a decrease in the number of flower buds generated by P. nil. Application of ethylene did not affected niether the level of endogenous jasmonates in the cotyledons during the 16 h long inductive night, nor the inhibitory effect of JA-Me on the flowering of P. nil accompanied by variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…6). The application of IAA stimulates the biosynthesis of JA, JAMe and ethylene, thus inhibiting flower induction of I. nil (Maciejewska et al 2004;Kęsy et al 2008Kęsy et al , 2010Kęsy et al , 2012Frankowski et al 2009). No response to exogenous IAA application, and consequently to an increase in the level of jasmonic acid, indicates that the expression of InTCP4 is not influenced by these phytohormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). The application of IAA stimulates the biosynthesis of JA, JAMe and ethylene, thus inhibiting flower induction of I. nil (Maciejewska et al 2004;Kęsy et al 2008Kęsy et al , 2010Kęsy et al , 2012Frankowski et al 2009). No response to exogenous IAA application, and consequently to an increase in the level of jasmonic acid, indicates that the expression of InTCP4 is not influenced by these phytohormones.…”
Section: Discussionmentioning
confidence: 99%
“…JA can thus affect the ''biological'' age of the cotyledons, and thus adjust the time sensitivity of plants to the inductive photoperiod. The I. nil study demonstrated that disruption of the endogenous level of JA during night inhibits the induction of flowering (Maciejewska et al 2004;Kęsy et al 2012); therefore we identify InTCP4 cDNA and Inpre-miR319 from I. nil cotyledons, observe its expression in various organs of plants and investigate the role of In-TCP4 in flowering induction. We also examine their participation in flower development and cotyledon senescence of I. nil.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in many plant species show that JAMe, formed in the reaction catalyzed by JASMONIC ACID CARBOXYL METHYLTRANSFERASE (JMT), regulates the sprouting of seeds, participates in proper flower morphogenesis and flower induction, and is involved in responses to stress, which also includes promoting effect on leaf senescence (Ananieva et al 2007;Kęsy et al 2011;Maciejewska and Kopcewicz 2002;Maciejewska et al 2004;Norastehnia et al 2007;Wang 1998;Wilson et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In our former investigation, we showed that JAMe is an inhibitor of photoperiodic flower induction in model short-day plant (SDP) Ipomoea nil, in which the cotyledons are responsible for the perception of light stimuli (Kęsy et al 2011;Maciejewska and Kopcewicz 2002;Maciejewska et al 2004). Bearing in mind the involvement of JAMe in the control of many processes, we conducted physiological experiments on the efficiency of PSII, changes in the jasmonate level, chlorophyll content and autofluorescence.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The results of research conducted on Spirodela polyrrhiza [16], Wolffia arrhiza [17], Nicotiana tabacum [18], and Chenopodium rubrum [19] show that jasmonates inhibit flower induction triggered by the photoperiod. Methyl jasmonate applied both to the cotyledons and roots or shoot apices before or during the 16-h-long inductive night inhibits flowering in Ipomoea nil, whereas JA does not affect that process [20][21][22]. Ipomoea nil is a preferential short-day plant (SDP), which can be induced to flower by a single photo inductive dark period.…”
Section: Introductionmentioning
confidence: 99%